Screening for pancreatic ductal adenocarcinoma in the population with diabetes. (1st February 2021) - Sharp, Patrick; Brown, Beata; Price, Hermione
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an uncommon condition with an incidence of about 8–12 cases per 100, 000 of the population per year. Presentation is often late, treatment outcomes poor and the mortality rate is high. There is no screening strategy for the condition at present. However, it is recognised that PDAC is associated with a rise in blood glucose in the months prior to diagnosis. Current NICE guidance recommends that imaging is considered in individuals over the age of 60 years who present with new onset diabetes. In this brief review we consider the background to this recommendation and how it might be incorporated into practice for diabetes health care professionals. The key point is to keep aware of the fact that a few of our patients with diabetes may have a background diagnosis of pancreatic cancer and to be vigilant for any possible red flag signs. Copyright © 2021 John Wiley & Sons.